2017
DOI: 10.1038/srep45492
|View full text |Cite
|
Sign up to set email alerts
|

ATHB17 enhances stress tolerance by coordinating photosynthesis associated nuclear gene and ATSIG5 expression in response to abiotic stress

Abstract: Photosynthesis is sensitive to environmental stress and must be efficiently modulated in response to abiotic stress. However, the underlying mechanisms are not well understood. Here we report that ARABIDOPSIS THALIANA HOMEOBOX 17 (ATHB17), an Arabidopsis HD-Zip transcription factor, regulated the expression of a number of photosynthesis associated nuclear genes (PhANGs) involved in the light reaction and ATSIG5 in response to abiotic stress. ATHB17 was responsive to ABA and multiple stress treatments. ATHB17-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 71 publications
2
34
0
1
Order By: Relevance
“…Homeobox homeodomain leucine-zipper (HD-Zip) TFs have diverse functions during plant development and stress adaptation, and some members of this family are under the control of the phytochrome system such as ARABIDOPSIS THALIANA HOMEOBOX 2 (ATHB2) (Kunihiro et al, 2011). ATHB17-overexpressing plants enhance abiotic stress tolerance by coordinating both photosynthesis-associated nuclear genes (PhANGs) involved in the light reactions and an essential nucleus-encoded Arabidopsis σ-Like Factor (AtSig5) (Zhao et al, 2017). The functional analysis of transgenic wheat overexpressing Nuclear Factor Y (TaNF-YB3) provided evidence for the positive involvement of the TF gene TaNF-YB3 in the regulation of photosynthesis genes leading to an increase in leaf chlorophyll content and photosynthetic rate (Stephenson et al, 2011).…”
Section: Photosynthesis and Transcriptional Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Homeobox homeodomain leucine-zipper (HD-Zip) TFs have diverse functions during plant development and stress adaptation, and some members of this family are under the control of the phytochrome system such as ARABIDOPSIS THALIANA HOMEOBOX 2 (ATHB2) (Kunihiro et al, 2011). ATHB17-overexpressing plants enhance abiotic stress tolerance by coordinating both photosynthesis-associated nuclear genes (PhANGs) involved in the light reactions and an essential nucleus-encoded Arabidopsis σ-Like Factor (AtSig5) (Zhao et al, 2017). The functional analysis of transgenic wheat overexpressing Nuclear Factor Y (TaNF-YB3) provided evidence for the positive involvement of the TF gene TaNF-YB3 in the regulation of photosynthesis genes leading to an increase in leaf chlorophyll content and photosynthetic rate (Stephenson et al, 2011).…”
Section: Photosynthesis and Transcriptional Regulationmentioning
confidence: 99%
“…Furthermore, photosynthesis is highly sensitive to abiotic stresses such as drought, high temperatures, and ozone, since they inactivate photosynthetic electron transfer and photophosphorylation, adversely affect photosynthetic metabolic processes, and lead to damage of thylakoid membranes and organelle ultrastructure (Ainsworth et al, 2013;Lobell et al, 2014;Sieber et al, 2016). In fact, an increase in atmospheric temperature can reduce crop yields by between 6 to 25% depending on the region and the crop (Sieber et al, 2016;Zhao et al, 2017). However, drought is the major abiotic stress that impairs crop production (Mishra and Cherkauer, 2010;Lobell et al, 2014;Lesk et al, 2016;Zipper et al, 2016;Matiu et al, 2017) due to photosynthetic limitations imposed by stomatal and non-stomatal processes (Tissue et al, 2005;Kohzuma et al, 2009;Dahal et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Nagashima et al [47] suggested SIG5 is involved in protecting chloroplasts under abiotic stress by promoting the repair of the PSII reaction center. Recently, Zhao et al [48] obtained transgenic lines overexpressing SIG5, which showed increased tolerance to salinity. As such, as these results show that both RPOTp-and PEP-mediated plastid transcription are involved in plant salt tolerance, we consider it feasible that PGE alteration at the transcriptional level may account for the abiotic stress phenotype of mutants sca3, mterf and sig5-2.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the regulation of plant growth and development, several of the class II HD-ZIP transcription factors have been also reported to participate in plant responding to exogenous ABA and drought stress. ATHB17 has been characterized as a positive regulator of ABA response and multiple stress responses [ 46 , 49 ]. ABIG1/HAT22 is induced by ABA and drought stress, and relays ABA signaled growth inhibition and drought induced senescence [ 50 ].…”
Section: Discussionmentioning
confidence: 99%